The Study of properties structure and some optical properties forcopper Oxid (CuO) Thin film prepared by thermal evaporation in Vacume (Baghdad Science Journal, 2004)
in this paper copper oxide (cuO thin films were prepared by the method of vacum thermal evaporation a pressure.